Shallow Groundwater Level Monitoring in the Kathmandu Valley: Investigating Citizen Scientist Performance and Groundwater Level Data Fluctuation - Mandal, Rohinee Bishwas; Acharya, Sangharsh; Adhikari, Sadhana; Rijal, Kaushal; Duwal, Sudeep; Neupane, Sanjiv (International Journal on Engineering Technology, 2025)
Shallow groundwater level monitoring is crucial for the sustainable management of water, particularly in rapidly growing cities like the Kathmandu Valley (Valley). Engaging local communities as citizen scientists (CS) offers cost-effective data collection and creates awareness about groundwater status and management practices. This study investigates the performance of citizen scientists (regularity and data submission error) in groundwater level monitoring and evaluating the groundwater fluctuation trend in the Valley. During 2020, 68% of the groundwater CS was categorized as regular. In 2021 and 2022, regularity increased to 91% compared to the previous years, and regularity decreased in 2023 and increased in 2024. Meanwhile, a rise in the percentage of CS sending incorrect data was observed. Despite these fluctuations, the overall error percentage was very low (